2009
DOI: 10.1063/1.3080660
|View full text |Cite
|
Sign up to set email alerts
|

In situ extended x-ray absorption fine structure study of initial processes in CdSe nanocrystals formation using a microreactor

Abstract: The nucleation process of CdSe nanocrystals is studied by fluorescence-detected extended x-ray absorption fine structure (EXAFS) using a microreactor and synchrotron radiation. Detailed analysis of in situ Se K-edge EXAFS data measured along a microreactor channel revealed a strong position-dependence which displays a rapid increase in the CdSe phase with time at the initial stage. The results indicate that the CdSe nucleation completes within several seconds starting from trioctylphosphine Se solution and dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 23 publications
0
36
1
Order By: Relevance
“…A different but also important study [45] also demonstrated the nucleation and the growth mechanism of the CdSe NPs using in situ fluorescence detected extended X-ray absorption spectroscopy (EXAFS) [46] and ex situ UV-Vis absorption techniques. The data collected via these two techniques were taken under the same conditions.…”
Section: In Situ Characterization Techniquesmentioning
confidence: 99%
“…A different but also important study [45] also demonstrated the nucleation and the growth mechanism of the CdSe NPs using in situ fluorescence detected extended X-ray absorption spectroscopy (EXAFS) [46] and ex situ UV-Vis absorption techniques. The data collected via these two techniques were taken under the same conditions.…”
Section: In Situ Characterization Techniquesmentioning
confidence: 99%
“…The synthesis of the CdSe QDs was modified from the original organometallic procedure [18] for utilization of the microfluidic reactor [9,17,19]. Three raw material stock solutions (Se source, Cd source and ligand solutions) were prepared under a dry nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…There are two peaks at approximately 1.7Å and 2.3Å without a phase shift. Based on previous results [21,31,[39][40][41], the Cd-Se bond has a peak between 2.0 and 3.2Å in the Cd K-edge RSF function. In our results, there is a peak at approximately 2.3Å without a phase shift, which was confirmed to be from the Cd-Se bond.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 64%